PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDS MUHAMMADIYAH KECAMATAN MANDAU - Ernewati Ernewati; Zariul Antosa; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: This research was conducted because of the result of learning Matematic class IV SDS Muhammadiyah From 26 student who achieve KKM just 10 student (38,46%) while student who did’nt complete 16 student (61,54 %) with an average of 59,28. This aims of study toincrease study result mathematic school years 2015-2016. This research subjet are class IV SDS Muhammadiyah Kecamatan Mandau with the whole student amount of 26 students. This research is the action research class with the two cycle. This case can prove with the activity teacher score are one cycle on the first appointment teacher activity reach 58 score with the enough category and can increase to 62,6 with the good category. And than two cycle on the first appointment can increase with 75 score good category and the secon appointment increase again with amount 83,3 with the excellent score category. Student activity have increase ae one cycle from the first appointment student activity can reach 54 score with the enough category and progress poin 4 to 58. The second appointment with the enough category. And than two cycle first appointment to increase axpesience. A lot of 75 score the good category. With the increased studies result have 10 student ( 38,46%) can completed and cycle exam daily have increase experience to 23 person (88,46%) and so the two cycle from daily exam two have increase satisfactory result are 25 student. If can applied Quantum Teaching Learning can progress studies result mathematic class IV student SDS Muhammadiyah Kecamatan Mandau.Keywords : Quantum Teaching, Learning Outcomes Mathematics